Determining the critical aiming window duration based on shooter skill level - Schnipke, J. R.; LaFiandra, M. E.; Freisinger, G. M.; Hasselquist, L.; Brown, S. A. T. (Proceedings of the Human Factors and Ergonomics Society Annual Meeting, 2019)
The fine-tuning phase of aiming directly prior to trigger pull has been hypothesized to influence shot accuracy, however there is little research exploring and distinguishing the different phases of motor control during aiming. This analysis seeks to establish a baseline model for determining the duration of the fine-tuning stage of target acquisition, or the critical aiming window (CAW). The study uses data collected from United States Army Soldier volunteers in a simulated firing event from two different stationary shooting positions (standing and kneeling). The method of investigation included calculation of velocity, acceleration, and jerk of the target marker over the course of aiming to identify trends indicative of a transition between shooting phases. While acceleration and jerk yielded inconclusive results, a significant decrease in velocity was identified during specific shooting positions. This model uses a function of average velocity throughout the shooting trial to determine the CAW.